PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PETUGAS REKAM MEDIS DI RSI “SITI HAJAR” DAN RSIA “PERMATA HATI” KOTA MATARAM - Rosita, Ulva Eti; Chaerunnisah, Reni; Istiqomah, Ria Rahmatul (Quality Assurance and Health Information Management, 2019)
Through this assessment, the actual condition of the officer’s performance can be known. The purpose of this study was to determine the relationship between workload and work environment with the performance of medical record officers at RSI "Siti Hajar" and RSIA "Permata Hati" Mataram city. This research is a quantitative analytical research carried out at RSI "Siti Hajar" and RSIA "Permata Hati" Mataram City. The population in this study were all medical record officers at RSI "Siti Hajar" and RSIA "Permata Hati" Mataram city. The sample in this study is the entire population, amounting to 30 people. Data collection is done by giving a questionnaire. The results of this study indicate that the majority of respondents rated the workload at RSI "Siti Hajar" and RSIA "Permata Hati" Mataram city as being in the high workload category with a percentage of 86.67%. Most of the respondents considered the work environment at RSI "Siti Hajar" and RSIA "Permata Hati" in Mataram city to be in the category of good work environment with a percentage of 93.33%. All respondents at the "Siti Hajar" RSI and "Permata Hati" RSIA Mataram city have performance that is included in the high category. The results of this study indicate that there is a relationship between workload and the performance of medical record officers at RSI "Siti Hajar" and RSIA "Permata Hati" Mataram city and there is a relationship between the work environment and medical performance. record officer at RSI "Siti Hajar" and RSIA "Permata Hati" Mataram city.